Study on Prediction of Outburst Risk of Excavation Face by Initial Gas Emission - Lu Gao; Xiangtao Kang; Meng Tang; Jinguo Hu; Jiachi Ren; Cunliu Zhou (Geofluids)
In order to improve the accuracy of coal and gas outburst risk prediction for an excavation face, an outburst equilibrium equation for the excavation face was established based on the Mohr–Coulomb criterion to predict the coal and gas outburst risk for the excavation face. The numerical model was established using the COMSOL Multiphysics simulation software to explore the relationship between the initial gas emissions from the borehole and the gas pressure. Using a ZTL20/1000-Z mine flameproof prediction device, taking excavation face 9301 in the Anshun Coal Mine in Guizhou Province, China, as the research object, and taking the detailed regulations for prevention and control of coal and gas outburst promulgated by the China Coal Mine Safety Supervision Bureau in 2019 as the prediction standard for coal and gas outbursts, an experiment on the outburst risk prediction for the excavation face was conducted. The results show that the gas pressure measured in the borehole is positively correlated with the initial gas emissions, and the initial gas flow can be used as a sensitive index to predict the outburst risk of the excavation face. The initial gas flow increases as the borehole depth increases, and it tends to be stable in the later stage. The initial borehole gas flow can not only reflect the outburst risk but also reveal the possible location of the outburst, which has obvious advantages over other outburst prediction indexes.